Legal Protection of Geographical Indications Concerning Nira Water in Dolog Huluan Village Dolog Masagal Pematang Raya District - Dian Uli Anatasia L Tobing; Anjelina Pasaribu; Bila May; Parlaungan Gabriel Siahaan; Reh Bungana Parangin angin (Universitas Muhammadiyah Enrekang, 2023)
Geographical Indication Protection aims to protect the uniqueness of a region's products, such as producers from certain regions which are famous for their sap water. usually they do not protect the quality of their regional products. This can open the door for other manufacturers in different locations to produce similar products and claim that their products come from the same area or have the same quality, when in fact they do not The Mini Research Assignment for Group 1 from class A PPKn stambuk 2021 is entitled: